Zooming In and Out: Connecting Individuals and Collectivities at the Frontiers of Organizational Network Research - Ibarra, Herminia; Kilduff, Martin; Tsai, Wenpin (Organization Science, 2005)
The role of individual action in the enactment of structures of constraint and opportunity has proved to be particularly elusive for network researchers. We propose three frontiers for future network research that zoom back and forth between individual and collective levels of analysis. First, we consider how dilemmas concerning social capital can be reconciled. Actors striving to reap maximal network advantages may benefit or detract from the collective good; investigating these trade-offs, we argue, will advance our understanding of learning and knowledge processes in organizations. Second, we explore identity emergence and change from a social network perspective. Insights about how networks mold and signal identity are a critical foundation for future work on career dynamics and the workplace experiences of members of diverse groups. Third, we consider how individual cognitions about shifting network connections affect, and are affected by, larger social structures. As scholarly interest in status and reputational signaling grows, articulating more clearly the cognitive foundations of organizational networks becomes imperative.